From disaster to devastation: drought as war in northern Uganda. (6th August 2018) - Branch, Adam
Abstract : This paper proposes a shift from the concept of disaster to one of devastation when dealing with the destructive consequences of climate change. It argues that today, a discourse of climate‐change disaster has become dominant, in which present disasters are seen as harbingers of a future of widespread climate disaster, products of a global nature in upheaval. The paper contends that one needs to go beyond the series of dichotomies that the climate‐change disaster discourse relies upon: future/past, global/local, natural/social. To frame climate disaster as a product of global climate change, and conflict the product of those climate disasters, is to occlude the forms of environmental violence and experience of climate change among disaster‐affected communities. Through an exploration of the drought in Uganda, the paper asserts that disaster should be understood as embedded within ongoing, longstanding, multiscalar processes of devastation produced by histories of human engagement with the environment, including that of war.